A kind of concrete admixture of deflocculant and preparation method thereof

By using anti-flocculant admixture in concrete and using components such as polyethyleneimine and polyethylene glycol for charge neutralization and cross-linking reactions, the problems of high viscosity and fluidity loss caused by excessive use of flocculant in mechanical sand are solved, and the effect of improving concrete fluidity and construction performance is achieved.

CN117486531BActive Publication Date: 2025-04-01CHINA CONSTR WEST CONSTR SOUTHWEST CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311425197.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-04-01
Estimated Expiration
2043-10-31

AI Technical Summary

Technical Problem

Excessive use of flocculant in machined sand results in high viscosity, rapid fluid loss and difficulty in construction of concrete mixture.

Method used

A concrete admixture with an anti-flocculant is used, and the composition includes polyethyleneimine solution, polyethylene glycol, composite catalyst aid, catalytic stabilizer and water. Through charge neutralization reaction and cross-link polymerization reaction, the adsorption effect of the flocculant on the concrete water reducing agent is weakened and the fluidity is improved.

Benefits of technology

It effectively reduces the adverse effects of flocculant on concrete, improves the flowability and flow retention time of concrete, improves construction performance, and has no significant impact on concrete strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005126022960000051
    Figure GDA0005126022960000051
  • Figure GDA0005126022960000052
    Figure GDA0005126022960000052
Patent Text Reader

Abstract

The present invention discloses a concrete admixture of an anti-flocculant, wherein the components and their weight percentages include: 60-70 parts of polyethyleneimine solution, 10-15 parts of polyethylene glycol, 0.1-1 parts of a composite catalyst aid, 4-10 parts of a catalyst stabilizer, and 15-25 parts of water; wherein the composite catalyst aid is obtained by compounding nano zinc oxide, cellulase, and amidohydrolase. The concrete admixture of the present invention can effectively solve the adverse effects of the flocculant on the concrete, such as high viscosity of the mixture, rapid loss of fluidity, and difficulty in construction, and the preparation method involved is relatively simple, easy to operate, and suitable for popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to a concrete admixture of an anti-flocculant and a preparation method thereof. Background Art

[0002] A large amount of clean water is required for washing in the production process of water-washed machine-made sand. In order to save water resources, an appropriate amount of flocculant is added during the washing process, which has led to the rapid development of the application of flocculants in water-washed machine-made sand. Anionic polyacrylamide (PAM) is a flocculant commonly used in water-washed machine-made sand. It can significantly accelerate the aggregation and sedimentation of solutes, colloids or suspension particles in aqueous solutions, thereby separating the excess stone powder and mud powder in the machine-made sand. However, the water washing process will produce a large amount of sand washing wastewater. In order not to pollute the environment, these wastewaters are usually filtered and reused, but the residual amount of flocculant is difficult to judge, which often leads to excessive flocculant remaining in the machine-made sand.

[0003] At present, the excessive use of flocculants in machine-made sand has caused problems such as high viscosity, rapid loss of fluidity and difficulty in construction of concrete mixtures produced by concrete enterprises. Therefore, it is of great research and application significance to study and develop a concrete admixture to solve the adverse effects of flocculants on concrete quality. Summary of the invention

[0004] The main purpose of the present invention is to provide a concrete admixture to address the problems and shortcomings of the prior art, which can effectively solve the adverse effects of flocculants on concrete, such as high viscosity of the mixture, rapid loss of fluidity and difficulty in construction. The preparation method involved is relatively simple, easy to operate and suitable for popularization and application.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] The invention discloses a concrete admixture of an antiflocculant. The components and their weight proportions include: 60-70 parts of polyethyleneimine solution, 10-15 parts of polyethylene glycol, 0.1-1 part of a composite catalyst assistant, 4-10 parts of a catalyst stabilizer and 15-25 parts of water.

[0007] In the above scheme, the concentration of the polyethyleneimine solution is 40-60wt%, and the molecular weight of the polyethyleneimine is 600-1800.

[0008] In the above scheme, the molecular weight of the polyethylene glycol is 200-400.

[0009] In the above scheme, the composite catalyst aid is composed of nano zinc oxide, cellulase, and amide hydrolase in a mass ratio of 2-3:0.5-1:1-2.

[0010] Furthermore, the particle size of the nano zinc oxide is 40 to 60 nm.

[0011] In the above scheme, the catalyst stabilizer is β-glucan, hydroxyethyl cellulose or gelatin.

[0012] The method for preparing the above-mentioned deflocculant concrete admixture comprises the following steps:

[0013] (1) adding polyethyleneimine aqueous solution and polyethylene glycol weighed according to the ratio into a reaction kettle;

[0014] (2) adding an alkaline buffer to adjust the pH value of the resulting mixed solution to 10-14, heating to 100-150° C. within 25-30 min; stirring at this temperature for 3-5 h, stopping heating, and cooling to room temperature;

[0015] (3) The weighed catalyst stabilizer, composite catalyst promoter and water are stirred evenly (20 to 30 minutes), and then added into the mixed solution obtained in step 2); mixed evenly to obtain the concrete admixture of the deflocculant.

[0016] In the above scheme, the alkaline buffer can be selected from sodium carbonate or potassium carbonate.

[0017] The application method of the above-mentioned anti-flocculant concrete admixture is: when the flocculant content in the machine-made sand is relatively high or the flocculant content fluctuates greatly, the dosage is 0.05-0.2% of the mass of the machine-made sand.

[0018] Furthermore, the flocculant is an anionic flocculant such as polyacrylamide.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1) The polyethyleneimine aqueous solution has a high cationicity and can react with anionic flocculants such as polyacrylamide in concrete to neutralize the charge, thereby weakening the adsorption of the flocculant on the concrete water reducer and enhancing the fluidity and flow retention time of the concrete; in addition, under the reaction conditions of the present invention, the imine of the polyethyleneimine reacts with the hydroxyl group in the polyethylene glycol to form a cross-linking polymerization reaction, and the high surface activity of the polyethylene glycol can improve the dispersion effect of the polyethyleneimine in the concrete, and the imine group is appropriately weakened after the reaction, which can further promote the polyethyleneimine molecules to be more dispersedly combined with the anionic flocculant;

[0021] 2) The composite catalyst used in the present invention can effectively promote the depolymerization of high molecular weight polymer flocculants such as polyacrylamide into low molecular weight complexes, reduce the macromolecular effect of the flocculant, and reduce the viscosity of the concrete; in addition, the molecular weight of commonly used flocculants such as polyacrylamide is usually in the millions or tens of millions. The present invention can promote the long chains of the flocculants to be wrapped by a large amount of polyethyleneimine with a molecular weight of 600 to 1800 and separated into "short chains". The connection between the "short chains" becomes a weak link. Combined with the composite catalyst, the depolymerization rate of flocculants such as polyacrylamide can be greatly improved;

[0022] 3) The introduced polysaccharide catalyst stabilizer forms a complex with the protein in the present invention, provides a protective effect, and can effectively delay the degradation and deactivation process of the composite catalyst. DETAILED DESCRIPTION

[0023] The present invention is not limited to the above-mentioned embodiments. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention. The contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field.

[0024] In the following examples, the particle size of the nano zinc oxide used is 40 to 60 nm.

[0025] Example 1

[0026] A concrete admixture of an anti-flocculant, comprising the following components: 60 parts (by weight, the same below) of a polyethyleneimine aqueous solution (molecular weight of 1800, concentration of 50%), 12 parts of polyethylene glycol (molecular weight of 400), 0.5 parts of a composite catalyst aid, 5 parts of a catalyst stabilizer β-glucan, and 20 parts of water; the composite catalyst aid comprises nano zinc oxide, cellulase, and amidohydrolase in a mass ratio of 3:1:1;

[0027] The specific preparation method is:

[0028] (1) putting the weighed polyethyleneimine aqueous solution and polyethylene glycol into a reaction kettle;

[0029] (2) adding sodium carbonate as an alkaline buffer, adjusting the pH value of the resulting mixed solution to 12, heating to 120° C. within 25 to 30 minutes; keeping warm and stirring for 4 hours, stopping heating, and cooling to room temperature;

[0030] (3) Stir the weighed catalyst stabilizer, composite catalyst promoter and water for 20 minutes, and then put them into the reactor described in step 2); stir and mix them evenly to obtain the concrete admixture.

[0031] Example 2

[0032] A concrete admixture of an anti-flocculant, comprising 65 parts (by weight, the same below) of a polyethyleneimine aqueous solution (molecular weight of 1800, concentration of 50%), 15 parts of polyethylene glycol (molecular weight of 200), 0.5 parts of a composite catalyst aid, 5 parts of a catalyst stabilizer β-glucan, and 20 parts of water; the composite catalyst aid is composed of nano zinc oxide, cellulase, and amidohydrolase in a mass ratio of 2:1:1.5;

[0033] The specific preparation method is:

[0034] (1) putting the weighed polyethyleneimine aqueous solution and polyethylene glycol into a reaction kettle;

[0035] (2) adding sodium carbonate as an alkaline buffer, adjusting the pH value of the resulting mixed solution to 12, heating to 120° C. within 25 to 30 minutes; keeping warm and stirring for 4 hours, stopping heating, and cooling to room temperature;

[0036] (3) Stir the weighed catalyst stabilizer, composite catalyst promoter and water for 20 minutes, and then put them into the reactor described in step 2); stir and mix them evenly to obtain the concrete admixture.

[0037] Example 3

[0038] A concrete admixture of an anti-flocculant, comprising the following components: 70 parts (by weight, the same below) of polyethyleneimine aqueous solution (molecular weight of 1800, concentration of 50%), 12 parts of polyethylene glycol (molecular weight of 400), 0.5 parts of a composite catalyst aid, 8 parts of a catalyst stabilizer β-glucan, and 20 parts of water; the composite catalyst aid comprises nano zinc oxide, cellulase, and amidohydrolase in a mass ratio of 2:1:1;

[0039] The specific preparation method is:

[0040] (1) putting the weighed polyethyleneimine aqueous solution and polyethylene glycol into a reaction kettle;

[0041] (2) adding sodium carbonate as an alkaline buffer, adjusting the pH value of the resulting mixed solution to 12, heating to 150° C. within 25 to 30 minutes; stirring at this temperature for 6 hours, stopping heating, and cooling to room temperature;

[0042] (3) Stir the weighed catalyst stabilizer, composite catalyst promoter and water for 20 minutes, and then put them into the reactor described in step 2); stir and mix them evenly to obtain the concrete admixture.

[0043] Example 4

[0044] A concrete admixture of an anti-flocculant, comprising the following components: 60 parts (by weight, the same below) of polyethyleneimine aqueous solution (molecular weight of 1800, concentration of 50%), 12 parts of polyethylene glycol (molecular weight of 400), 0.5 parts of a composite catalyst aid, 5 parts of a catalyst stabilizer β-glucan, and 20 parts of water; the composite catalyst aid comprises nano zinc oxide, cellulase, and amidohydrolase in a mass ratio of 2:0.5:1;

[0045] The specific preparation method is:

[0046] (1) putting the weighed polyethyleneimine aqueous solution and polyethylene glycol into a reaction kettle;

[0047] (2) adding sodium carbonate as an alkaline buffer, adjusting the pH value of the resulting mixed solution to 12, heating to 120° C. within 25 to 30 minutes; keeping warm and stirring for 4 hours, stopping heating, and cooling to room temperature;

[0048] (3) Stir the weighed catalyst stabilizer, composite catalyst promoter and water for 20 minutes, and then put them into the reactor described in step 2); stir and mix them evenly to obtain the concrete admixture.

[0049] Example 5

[0050] A concrete admixture of an anti-flocculant, comprising the following components: 60 parts (by weight, the same below) of polyethyleneimine aqueous solution (molecular weight of 1800, concentration of 50%), 12 parts of polyethylene glycol (molecular weight of 400), 0.5 parts of a composite catalyst, 5 parts of a catalyst stabilizer β-glucan, and 15 parts of water; the composite catalyst aid comprises nano zinc oxide, cellulase, and amidohydrolase in a mass ratio of 2:1:1;

[0051] The specific preparation method is:

[0052] (1) putting the weighed polyethyleneimine aqueous solution and polyethylene glycol into a reaction kettle;

[0053] (2) adding sodium carbonate as an alkaline buffer, adjusting the pH value of the resulting mixed solution to 12, heating to 100° C. within 25 to 30 minutes; stirring at this temperature for 3 hours, stopping heating, and cooling to room temperature;

[0054] (3) Stir the weighed catalyst stabilizer, composite catalyst promoter and water for 20 minutes, and then put them into the reactor described in step 2); stir and mix them evenly to obtain the concrete admixture.

[0055] Example 6

[0056] A concrete admixture of an anti-flocculant, comprising the following components: 60 parts (by weight, the same below) of polyethyleneimine aqueous solution (molecular weight of 1800, concentration of 50%), 12 parts of polyethylene glycol (molecular weight of 400), 1 part of a composite catalyst, 10 parts of a catalyst stabilizer β-glucan, and 15 parts of water; the composite catalyst aid comprises nano zinc oxide, cellulase, and amidohydrolase in a mass ratio of 2:1:1;

[0057] The specific preparation method is:

[0058] (1) putting the weighed polyethyleneimine aqueous solution and polyethylene glycol into a reaction kettle;

[0059] (2) adding sodium carbonate as an alkaline buffer, adjusting the pH value of the resulting mixed solution to 12, heating to 120° C. within 25 to 30 minutes; keeping warm and stirring for 3 hours, stopping heating, and cooling to room temperature;

[0060] (3) Stir the weighed catalyst stabilizer, composite catalyst promoter and water for 20 minutes, and then put them into the reactor described in step 2); stir and mix them evenly to obtain the concrete admixture.

[0061] Comparative Example 1

[0062] The raw materials and method of this comparative example are basically the same as those of Example 1, except that no polyethylene glycol is added.

[0063] Comparative Example 2

[0064] The raw materials of this comparative example are basically the same as those of Example 1, except that the heating and stirring step described in step (2) is not performed. The specific steps of step (2) are: sodium carbonate is added as an alkaline buffer, and the pH value of the obtained mixed solution is adjusted to 12.

[0065] Comparative Example 3

[0066] The raw materials and method of this comparative example are basically the same as those of Example 1, except that the molecular weight of polyethyleneimine is 10,000.

[0067] The deflocculant concrete admixture (hereinafter referred to as deflocculant) prepared in the above embodiments and comparative examples was used for concrete test, and the amount of deflocculant was 0.1% of the mass of machine-made sand. In order to simulate the effect of flocculant on the working performance of concrete, an anionic polyacrylamide flocculant (PAM) with a molecular weight of 12 million and accounting for 0.05% of the mass of machine-made sand was added to the concrete mixing water. The concrete benchmark ratio is shown in Table 1, wherein the cement grade used is P·O 42.5, the fly ash is Class I fly ash, and the machine-made sand is Lafarge stone powder sand (detected to contain no flocculant). According to GB / T 50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures", the slump and expansion of the concrete at the beginning and 2h were tested.

[0068] Table 1 Concrete standard mix ratio (kg / m 3 )

[0069] cement Fly ash Machine-made sand gravel water Admixtures 260 60 960 980 160 5.0

[0070] Table 2 Test information (kg / m 3 )

[0071]

[0072] In Table 2, blank group 1 is the one without adding PAM and deflocculant to the base ratio, and blank group 2 is the one without adding deflocculant to the base ratio.

[0073] Table 3 Concrete working performance

[0074]

[0075] It can be seen from the above results that, based on the blank group 1, the blank group 2 added PAM to the concrete, and the fluidity of the concrete was significantly deteriorated, and it could not be pumped for construction. The fluidity of the concrete with the admixtures described in Examples 1 to 6 was close to that of the blank group 1. From the strength data, the blank group 2 had low fluidity and uneven molding, and the 7d and 28d strengths were both low, which did not meet the C30 design requirements. After adding the admixtures described in Examples 1 to 6, the strength performance of the resulting concrete can be effectively guaranteed. PAM was not added to the concrete mix described in Example 1, and the fluidity of the concrete was close to that of the blank group 1, indicating that the admixture of the present invention has strong adaptability, and even if it is added to concrete without PAM, it has no obvious effect on the fluidity and strength of the concrete, which is conducive to the use of the machine-made sand when the flocculant content is large or the flocculant content fluctuates greatly.

[0076] In Comparative Example 1, polyethylene glycol was not introduced, and the polyethyleneimine had insufficient dispersion effect and could not be fully combined with the flocculant. Instead, it additionally absorbed the water reducer in the concrete, resulting in poor fluidity of the concrete, poor uniformity of the formed concrete, and strength that did not meet the requirements. In Comparative Example 2, the heating and stirring step described in step (2) of Example 1 was not performed. The dispersion effect of polyethyleneimine was slightly better than that of Comparative Example 1, but still poor, with rapid fluidity loss and unsatisfactory strength. In Comparative Example 3, the introduction of polyethyleneimine with a larger molecular weight into the admixture increased the viscosity of the concrete, reduced fluidity, and the strength was slightly lower than that of the example.

[0077] The above results show that the present invention has a good inhibitory effect on flocculants, can improve the fluidity of concrete, increase construction efficiency, and has no obvious effect on the strength of concrete.

[0078] The present invention is not limited to the above-mentioned embodiments. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention. The contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field.

Claims

1. A concrete admixture of a deflocculant, characterized in that: The components and their weight proportions include: 60-70 parts of polyethyleneimine solution, 10-15 parts of polyethylene glycol, 0.1-1 parts of composite catalyst promoter, 4-10 parts of catalyst stabilizer, and 15-25 parts of water; The molecular weight of the polyethyleneimine is 600-1800; The composite catalyst aid is composed of nano zinc oxide, cellulase and amide hydrolase in a mass ratio of 2-3:0.5-1:1-2.

2. The concrete admixture according to claim 1, characterized in that: The concentration of the polyethyleneimine solution is 40-60wt%.

3. The concrete admixture according to claim 1, characterized in that: The molecular weight of the polyethylene glycol is 200-400.

4. The concrete admixture according to claim 1, characterized in that: The particle size of the nano zinc oxide is 40-60 nm.

5. The concrete admixture according to claim 1, characterized in that: The catalytic stabilizer is β-glucan, hydroxyethyl cellulose or gelatin.

6. The method for preparing the concrete admixture of the deflocculant according to any one of claims 1 to 5, characterized in that: The steps include: (1) Mixing polyethyleneimine solution and polyethylene glycol weighed according to the ratio; adding an alkaline buffer to adjust the pH value to alkaline; (2) heating the obtained mixed solution, stirring it while keeping it warm, and then cooling it to room temperature; (3) The weighed catalyst stabilizer, composite catalyst promoter and water are stirred evenly, and then added to the mixed solution obtained in step (2); the mixture is mixed evenly to obtain a concrete admixture of a deflocculant.

7. The preparation method according to claim 6, characterized in that: Step 1) Adjust the pH to 10-14.

8. The preparation method according to claim 6, characterized in that: The temperature of the heat preservation and stirring treatment is 100-150° C. and the time is 3-5 hours.

Citation Information

Patent Citations

  • Flocculating agent for underwater non-dispersing concrete

    CN110054434A

  • Preparation method of functional polycarboxylate-type water reducing agent for resisting flocculating agent in machine-made sand

    CN112661913A